Biblical Safeguards and Traditions as Potential Guidance for the Lending of Monies - Lippman, Ellen J. (Journal of business ethics, 2008)
Some individuals and businesses have become increasingly dependent upon multiple financing sources for economic survival. Certain currently used lending policies, such as interest-only loans and revolving credit lines, may encourage borrower dependency on the lender. The paper reviews religious teachings, specifically religious safeguards on lending identified in primary Jewish sources including the Tanach and rabbinic teachings, and finds that the safeguards in place centuries ago may still be relevant for lending practices today to both protect the borrower while still providing a profitable means to help borrowers.